Understanding university : a guide to another planet - Sinclair, Christine (Open University Press, 2006)
Does university seem like another planet? Does everyone else seem to speak another language? What can you do to make the grade? If these are the kind of questions you are asking, then this is the book you need. After the excitement of being accepted, the reality of life at university or college can be daunting, but help is at hand. This practical book guides new students through the terminology used at university and shows you: what a student needs to know how to be accepted by students and lecturers; how to get the best out of your institution and yourself; how to communicate using appropriate language in higher education institutions; how to learn the conventions of your specific subject area; and, how to be confident and competent in your new world. All new students find the move to university slightly bewildering, but with this book you can be one step ahead. The author has spent time talking to students across a broad range of different universities and uses her first-hand experience as a basis for the book.; "Understanding University" provides a lifeline for new students in further and higher education offering everything from practical advice on studying, to explanations of frequently used terms. If you don't know the difference between a seminar and a tutorial or want to know what 'matriculation' means, then this is where to start. Need a little assistance? Just open this book. And remember - you are not alone.